Petrography &Mineralogy of the Dammam Formation in Al-Najaf Governorate - Kadihm Al-Habeeb, Noor Khaleel; Abbas Al-Shammary, Thamer (Iraqi Journal of Science, 2023)
The Dammam Formation ( Middle-Late Eocene) has a total thickness 150 m , 143 m and 89.7 m at the studied wells (B.H.8, B.H.3 and B.H.1) respectively. They are located in Al- Najaf Governorate, 35 Km southwest of Al-Najaf city. The petrographic components of the Dammam limestone comprises skeletal grainsforaminifera (both benthic and planktonic), echinoderm plates and Mollusca, shell fragments, Bryozoan, Bioclasts are common, non-skeletal grainsare pellets, lithoclast (carbonate and non carbonate), and groundmass (micrite and sparry calcite). In term of mineralogy, the X-Ray analysis shows the presence of non clay minerals is calcite, dolomite as the main minerals and quartz and scattered evaporate, whereas clay minerals as secondary minerals are (palygorskite, montmorillonite, chlorite, kaolinite, illite).